Analisis Kesulitan Belajar Matematika di Rumah Selama Pandemi Covid-19 pada Siswa Kelas IV Sekolah Dasar - Suntari, Suntari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to describe the purpose of this study is to identify problems in learning mathematics at home during the Covid-19 pandemic that occurred in fourth grade students at SDN Jejeruk in the 2019/2020 school year. The focus of the research in writing this thesis is the method used in this research is descriptive qualitative with a phenomenological approach. The data sources of this study were all fourth grade students, parents, and fourth grade students teachers. Data collection techniques were carried out using questionnaires, interviews, and documentation studies. The validity test of the data used in this research is technical triangulation and source triangulation. Data analysis using Miles and Huberman data analysis model. The results of this study indicate that student learning problems occur because students have difficulty understanding concepts, difficulty solving problems in story problems, and difficulties in numeracy skills. Problem identification is carried out on Fractions material. Difficulty understanding concepts as much as 78%, difficulty in solving story problems as much as 90%, and difficulty in calculating number operations as much as 85%. The problems that occur are caused by several factors.